Income Analysis and the Effect of Production Factors on the Productivity of Long Bean Farming in Tongkuno District, Muna Regency - Citrahayu Diat Ningsih; Abdi, Abdi; La Ode Alwi (International journal of technology and education research, 2024)
This study aims to determine the income of long bean farmers in Tongkuno District, Muna Regency and to determine the effect of production factors on the productivity of long bean farming in Tongkuno District, Muna Regency. The determination of the research location was carried out by simple random sampling with a total of 46 respondents. Data analysis using income analysis and cobb-douglas production function, t test (partial), F test (simultaneous) and coefficient of determination (R2). The results showed that the income of long bean farming was Rp131,106,076/planting season with an average total of Rp2,850,131/planting season. For the production function, it simultaneously shows that the variables of land area, seeds, urea fertilizer, NPK fertilizer, pesticides, labor, and capital have a significant effect on the productivity of long bean farming with a sig of 0.000 <0.1, a calculated F value of 16.158, a correlation coefficient (R) of 0.865 and a determination coefficient value (R2 ) of 0.749. Partially, the variables of land area, pesticides, and labor have a significant effect on the productivity of long bean farming, while the variables of seeds, urea fertilizer, NPK fertilizer, and capital do not have a significant effect on the productivity of long bean farming